Management of Patients With Glucocorticoid-Related Diseases and COVID-19 - Chifu, Irina; Detomas, Mario; Dischinger, Ulrich; Kimpel, Otilia; Megerle, Felix; Hahner, Stefanie; Fassnacht, Martin; Altieri, Barbara (Frontiers in Endocrinology, 2021)
The ongoing coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a global health crisis affecting millions of people worldwide. SARS-CoV-2 enters the host cells by binding angiotensin-converting enzyme 2 (ACE2) after being cleaved by the transmembrane protease serine 2 (TMPRSS2). ACE2 is also extensively expressed in endocrine tissues, including the pituitary and adrenal glands. Although glucocorticoids could play a central role as immunosuppressants during the cytokine storm, they can have both stimulating and inhibitory effects on immune response, depending on the timing of their administration and their circulating levels. Patients with adrenal insufficiency (AI) or Cushing’s syndrome (CS) are therefore vulnerable groups in relation to COVID-19. Additionally, patients with adrenocortical carcinoma (ACC) could also be more vulnerable to COVID-19 due to the immunosuppressive state caused by the cancer itself, by secreted glucocorticoids, and by anticancer treatments. This review comprehensively summarizes the current literature on susceptibility to and outcome of COVID-19 in AI, CS and ACC patients and emphasizes potential pathophysiological mechanisms of susceptibility to COVID-19 as well as the management of these patients in case of SARS-CoV-2 infection. Finally, by performing an in silico analysis, we describe the mRNA expression of ACE2, TMPRSS2 and the genes encoding their co-receptors CTSB, CTSL and furin in normal adrenal and adrenocortical tumors (both adenomas and carcinomas).